Ethnobotanical Study of Cangkuang Plants (Pandanus furcatus Roxb.) in the Indigenous Community of Kampung Pulo Garut - Lida Amalia; Fitriani Dewi Sontani; Siti Nurkamilah (Journal Civics And Social Studies, 2021)
Ethnobotanical Study of Cangkuang Plants (Pandanus furcatus Roxb.) in the Indigenous Community of Kampung Pulo Garut. The aim is to find out the ethnobotany of Cangkuang plants through several studies, as well as knowing the percentage of growth strata, parts of the organs used, and their utilization. The benefit of research is to provide information about ethnobotany from various aspects of study and to inspire people to cultivate Cangkuang plants. The research method uses descriptive qualitative methods, work methods are carried out directly in the field and supported by respondent interviews (semi-structural and open ended). Determining respondents and collecting plant sample data used the purposive sampling method. Based on research, observations and interviews, the botanical study of the Cangkuang plant has the morphology of elongated pointed leaves, spiny edges, has stilt roots, and no flower shape can be found. Ethnopharmacology, leaves and fruit as medicine for diarrhea, dysentery, antioxidant. Ethnolinguistically, Cangkuang is used as the name of villages, lakes, temples and tourist parks. Ethnoanthropology, the fruit has a myth of being able to ward off spirits. Ethnoeconomically, the leaves are useful as household utensils and food packaging. Percentage of growth stages/strata, seedlings 68%, saplings 16%, poles 9%, and trees 7%. The percentage of plant parts that are used, leaves 83% and fruit 17%. Percentage of plant use, 50% as medicine, 30% as food packaging, 17% as household utensils, and 3% as mythical objects.